2019
DOI: 10.21276/ijcmr.2019.6.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Outcome of Neonates with Hypernatremic Dehydration - A Tertiary Care Hospital based Study

Abstract: Introduction: Neonatal hypernatremic dehydration is a medical emergency. Early diagnosis and appropriate treatment is crucial for survival and better prognosis. However, diagnosis is often difficult due to apparent well being and dehydration is underestimated. The aim of our study was to see the outcome of neonates admitted with hypernatremic dehydration in our hospital Material and Methods: The study was conducted in neonatology of Postgraduate Department of Pediatrics, in GB Pant Hospital, an associated hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
2
4
1
Order By: Relevance
“…Our observation is similar to other studies. 14 Mean weight loss was observed to be 15.6% and 57.7% of newborns had weight loss more than 15% which is in concordance with studies reporting that newborn presenting at a later age have more severe weight loss and hypernatremia. 15 At admission poor feeding, fever, jaundice, and dehydration were common symptoms in 85% of newborns.…”
Section: Discussionsupporting
confidence: 87%
“…Our observation is similar to other studies. 14 Mean weight loss was observed to be 15.6% and 57.7% of newborns had weight loss more than 15% which is in concordance with studies reporting that newborn presenting at a later age have more severe weight loss and hypernatremia. 15 At admission poor feeding, fever, jaundice, and dehydration were common symptoms in 85% of newborns.…”
Section: Discussionsupporting
confidence: 87%
“…Fever and lethargy were the other 2 commonly noted symptoms. Studies done in the past 10,18,20 also observed similar signs and symptoms in these infants. However, acute kidney injury was observed in most infants, but decreased urine output was a symptom only in 7.3% of cases.…”
Section: Discussionsupporting
confidence: 73%
“…The prevalence noted in our study was much higher as compared with the previous studies, which reported the prevalence as 1.3% and 3.4%, respectively. 2,10 The varied prevalence is attributed to variable inclusion criteria in different studies. The study done by Bhat et al 10 included all neonates admitted to the hospital (noncritical as well those with critical illness) as the denominator to calculate the prevalence, unlike our study in which we included those infants who met the screening signs and symptoms of hypernatremic dehydration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations